Impact of frequency of milking on milk yield and fertility of Holstein cows undergoing extended lactations due to failure to conceive - Mellado, Jesús; Flores, Jessica; Véliz, Francisco G.; Santiago, Ángeles de; García, José E.; Gutierrez, Hugo L.; Mellado, Miguel (Emirates Journal of Food and Agriculture, 2021)
The objective of this observational study was to determine the effect of two (2x) compared to three (3x) times a day milking in Holstein cows undergoing lactations ≥600 d on milk production and reproductive performance. Two large adjacent commercial dairy herds with similar size, facilities, and management in a hot area of northern Mexico (25° N) were used. Cows in one herd (n= 214) were milked two times a day (2x), the other herd was milked three times a day (3x; n=245) and both groups were milked for at least 600 days. For cows in first lactation, total milk yield did not differ between 3x and 2x cows (19796 ± 3354 vs. 19269 ± 3652 kg; p > 0.10) in lactations with an average of 696 and 650 days in milk (DIM), respectively. Multiparous 3x cows produced more total milk days than 2x cows (20942 ± 3920 vs. 18910 ± 2632 kg; p < 0.01) with greater (p < 0.01) DIM for 3x (685 ± 117 days) than 2x (631 ± 88 days) cows. Lactation persistence was greater (p < 0.05) in 2x (62 ± 9%) than 3x (60 ± 10%) cows. Overall conception rate (CR) did not differ between 2x and 3x cows (53.3% vs. 49.8%) but 3x cows required one more service (p < 0.01) to get pregnant than 2x animals. Given that average milk yield throughout the complete lactation did not differ between 2x (29.8 ± 2.0 kg) and 3x (29.3 ± 2.9 kg) cows, it was concluded that two-times-a-day milking is equally effective as three-times-a-day milking to attain acceptable milk yield in lactations over 600 days. However, reproductive performance based on first-service CR and services per pregnancy was negatively affected by three-times-a-day milking.